Promoting digital inclusion: challenges and promises on the arrival of digital television to Colombia - Zapata Duque, Jorge Fernando (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
The following is an analysis of the challenges and limitations that the arrival of the terrestrial digital television to Colombia faces as an opportunity for the promotion and develoment of processes aimed to enhance social inclusión. In particular, regarding the field of education in the contexto of the so-called Digital Divide. The reflections raised here depart from the hypotheses that, digital telecision as a convergent technology with great potential, given the fact that it can integrate services such as connectivity and interactivity, represents a suitable platform to offer education alternatives to those sectors of the population that do not count on Access to internet or other information and communication technologies. This análisis was made on the basis of a revision of studies dedicated to the comprehension on how digital televisión can be used for education purposes and processes aimed to promote social inclusión. Literature regarding problems such as how and to what extent,DTV has been used with these intentions in other countries has also been reviewed